Design of renewable poly(amidoamine)/hemicellulose hydrogels for heavy metal adsorption. Issue 12 (18th November 2014) - Ferrari, Elena; Ranucci, Elisabetta; Edlund, Ulrica; Albertsson, Ann‐Christine
ABSTRACT Renewable poly(amidoamine)/hemicellulose hydrogels were prepared from O‐acetylated galactoglucomannan (AcGGM)‐rich biomass and shown to display a significantly high adsorption capacity for Cu2+, Cd2+, Pb2+, Zn2+, Ni2+, Co2+, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2t6htn5g" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CrO42‐</alternatives>. Two different acrylamido end‐capped poly(amidoamine) oligomers (PAA) were prepared and covalently immobilized onto an in situ formed polysaccharide network via water‐based free radical graft copolymerization and cross‐linking. The synthetic approach was shown to be viable when using a highly purified AcGGM or a crude spruce hydrolysate, an AcGGM and lignin containing biomass fraction as a reactant. Homogeneous reaction mixtures were obtained in both cases with polysaccharide contents up to 20% by weight. Oscillatory shear measurements indicated a predominantly solid‐like behavior of the hydrogels with an increase in shear storage modulus with increasing cross‐link density. The mechanical integrity of the PAA/hemicellulose hydrogels showed higher water swelling capacity and less fragility than the parent PAA hydrogels and they retained the heavy metal ion absorption ability of the PAA component, even in the presence of the least purified hemicellulose fraction. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41695.